Decentralized Adaptive Pi With Adaptive Interaction Algorithm Of Wastewater Treatment Plant - Rahmat, Mohd Fua'ad; Rahmat, Mohd Fuaad; Abdul Wahab, Norhaliza; Che Razali, Mashitah; Gaya, Muhammad Sani; Samsudin, Sharatul Izah (Universiti Teknologi Malaysia, 2014)
Wastewater treatment plant (WWTP) is highly known with the variation and uncertainty of the parameters, making them a challenge to be tuned and controlled.In this paper, an adaptive decentralized Pi controller is developed for nonlinear activated sludge WWTP. The work is highlighted in auto-tuning the PI control parameters in satisfying straighten effluent quality and hence optimizing the nitrogen removal. The Pi controller parameters are obtained by using simple updating algorithm developed based on adaptive interaction theory. The error function is minimized directly by approximate Frechet tuning algorithm without explicit estimation of the model. The effectiveness of the proposed controller is then validated by comparing the performance of activated sludge process to the benchmark Pi under three different weather conditions with realistic variations in influent flow rate and composition. The algorithm is effectively applied in activated sludge system with improved dynamic performances in effluent quality index and energy consumed of Benchmark Simulation Model No.1.